ANALISIS KEBUTUHAN MODUL PEMBELAJARAN TETEDUHAN BERBASIS PROJECT-BASED LEARNING DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - Sari, Renielda; Ariyani, Farida; Samhati, Siti; Fuad, Muhammad (Universitas Lampung, 2024)
The use of teaching materials and instructional media that suit students' needs is often overlooked by teachers. However, various types of teaching materials and media can be utilized to support learning. This research is part of a developmental study aimed at analyzing the need for a shading learning module based on project-based learning to improve the learning outcomes of elementary school students. Data collection was carried out through interviews and questionnaires given to fifth-grade students and teachers at SDN 1 Sukabumi Indah. The preliminary research results, based on the needs analysis, indicate that students need a Lampung language learning module to support the learning process. Meanwhile, teachers have not been using modules in their teaching; instead, they rely on products obtained from publishers, resulting in learning activities that are not tailored to the needs of the students.Penggunaan bahan ajar dan media pembelajaran yang sesuai dengan kebutuhan seringkali diabaikan oleh guru. Padahal berbagai jenis bahan ajar dan media dapat dimanfaatkan untuk menunjang pembelajaran. Penelitian ini merupakan bagian dari penelitian pengembangan yang bertujuan untuk menganalisis kebutuhan modul pembelajaran teteduhan berbasis project-based learning dalam meningkatkan hasil belajar peserta didik sekolah dasar. Pengumpulan data dilakukan dengan wawancara dan pemberian kuesioner kepada peserta didik kelas V dan guru di SDN 1 Sukabumi Indah. Adapun hasil penelitian pendahuluan berdasarkan analisis kebutuhan yang diperoleh menunjukkan bahwa peserta didik membutuhkan modul pembelajaran bahasa Lampung untuk menunjang proses pembelajaran sementara guru belum menggunakan modul dalam pembelajaran, melainkan menggunakan produk yang didapat dari penerbit sehingga kegiatan pembelajaran tidak disesuaikan dengan kebutuhan peserta didik.